Analisis pengaruh profitabilitas, likuiditas, ukuran perusahaan, dan struktur modal terhadap nilai perusahaan - Ristiani, Lina; Sudarsi, Sri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine and analyze the effect of profitability (ROA), liquidity (CR), firm size (SIZE), and capital structure (DER) on firm value (Tobin's Q). The population used in this study is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in three periods, namely 2017-2020. The sampling method used in this study was purposive sampling, so that a total of 440 samples were obtained. The analytical method in this study is multiple linear regression analysis using IBM SPSS 26 software. The results of this study indicate that profitability (ROA) and firm size (SIZE) have a positive and significant effect on firm value (Tobin's Q), while liquidity (CR) and capital structure (DER) has no effect on firm value (Tobin's Q).